FAKTOR-FAKTOR YANG MEMPENGARUHI MANAJEMEN LABA PADA PERUSAHAAN SUB SEKTOR OTOMOTIF DAN KOMPONEN YANG TERDAFTAR DI BURSA EFEK INDONESIA (Periode 2010-2015) - Syarifah Rabi’ah Andawiyah; Astri Furqani (Fakultas Ekonomi dan Bisnis, 2016)
Earnings management in a practical level is the deliberate actions carried out by the company's management to affect earnings in the process of preparation of financial statements that are used to assess a company and usually management provides information about the economic benefits which were not experienced by the company for personal purposes as well as to increase the value of the company. This study aimed to examine the effect of the Return on Assets (ROA), institutional ownership, the percentage of public shares, the board of directors, audit committees and leverage partially or simultaneously on earnings management during the period 2010-2015. The population in this study is a sub company's automotive sector and the components listed in the Indonesia Stock Exchange by using purposive sampling method. Data were analyzed using multiple linear regression analysis. The results of hypothesis shows that (1) partially there is influence between the Return on Assets (ROA), commissioners and leverage to earnings management, but there is no influence between institutional ownership, the percentage of public shares and the audit committee on earnings management (2) is simultaneously a influence between the return on Assets (ROA), institutional ownership, the percentage of public shares, the board of directors, audit committees and leverage to earnings management.Keywords: earnings management, Return on Assets (ROA), institutional ownership, the percentage of public shares, the board of directors, audit committee, leverag